Impact of structure and homo-coupling of the central donor unit of small molecule organic semiconductors on solar cell performance. Issue 38 (31st March 2016) - Verstappen, Pieter; Cardinaletti, Ilaria; Vangerven, Tim; Vanormelingen, Wouter; Verstraeten, Frederik; Lutsen, Laurence; Vanderzande, Dirk; Manca, Jean; Maes, Wouter
Abstract : Next to the molecular structure, homo-coupling of the central donor moiety has a profound influence on organic solar cell efficiency. Abstract : Currently, both low bandgap conjugated polymers and small molecule analogues are employed as electron donor components in state of the art bulk heterojunction organic photovoltaics, providing similar record efficiencies (∼10%). However, to evaluate molecular structure-device performance relations and (in particular) the effect of material purity, small molecule chromophores can be considered to be more versatile probes. In the present study, we have synthesized three small molecule donor materials with a varying central electron-rich building block, inspired by the well-known high-performance small molecule p-DTS(FBTTh2 )2 . The influence of this structural modification on the physicochemical material properties, electro-optical characteristics and solar cell performance is analysed. Most importantly, it is shown that the presence of homo-coupled side products generated during Stille cross-coupling reactions – which can be very hard to remove, even for small molecule semiconductors – is detrimental to solar cell performance, with a noticeable effect on the open-circuit voltage.